Do Financial Incentives for Firms Promote Employment of Disabled Workers? A Regression Discontinuity Approach - Rafael Lalive; Jean-Philippe Wuellrich; Josef Zweimüller (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2009)
We study the impact of employment quota on firms' demand for disabled workers. The Austrian Disabled Persons Employment Act (DPEA) requires firms to provide at least one job to a disabled worker per 25 non-disabled workers, a rule which is strictly enforced by non-compliance taxation. We find that, as a result of the discontinuous nature of the noncompliance tax, firms exactly at the quota threshold employ 0.05 (20 % in relative terms) more disabled workers than firms just below the threshold an effect that is unlikely driven by purposeful selection below the threshold. The flat rate nature of the non-compliance tax generates strong employment effects for low-wage firms and weak effects for high-wage firms. We also find that growing firms passing the quota threshold react with a substantial time-lag but the magnitude of the long-run effect is similar to the one found in cross-section contrasts.
Keywords: J15; J20; J71; J78; 330; disability; discrimination; employment; employment quota; regression discontinuity